Empowering the KWT Rejoarum Group through the Implementation of Drip Irrigation as an Innovative Solution for Water Efficiency and Capacity Building - Subrata, Arsyad Cahya; Juwitaningtyas, Titisari; Ikawati, Retty; Rahmawan, Azfa; Mahira, Amiresti Hakimatul; Fauzia, Ainin Nuzha Izzatin; Hakim, Haidar Usman; Nurbaiti, Fityatul (UKInstitute, 2026)
The Rejoarum Women Farmers Group (KWT) in Pandowoharjo, Sleman, faces challenges in cultivating California papaya due to its dependence on an inefficient traditional irrigation system. The main problems include water wastage, high operational costs, and dependence on weather conditions, which affect the group's productivity and income. This community service program aims to improve irrigation efficiency and partner capacity through the participatory application of drip irrigation technology. The method used is participatory action, which actively involves group members in all stages of the program, from planning and installation to system evaluation. The results show that the drip irrigation system was successfully installed on 1,000 m² of land and is operating optimally. Pre-test and post-test analyses reveal a 14% increase in the group members' understanding and technical skills in operating and maintaining the system. The participatory approach has proven effective in building the group's independence, increasing water use efficiency, and reducing operational costs. This program not only solved technical irrigation problems but also empowered partners through direct learning processes and local capacity building. The sustainability of the program is ensured through the commitment and sense of ownership of the partners towards the technology applied, as well as plans for replication in other farmer groups.